Dose-escalated intensity-modulated radiotherapy in patients with locally advanced laryngeal and hypopharyngeal cancers: ART DECO, a phase III randomised controlled trial. (August 2021) - Nutting, Christopher M.; Griffin, Clare L.; Sanghera, Paul; Foran, Bernadette; Beasley, Matthew; Bernstein, David; Cosgrove, Vivian; Fisher, Shelia; West, Catherine M.; Sibtain, Amen; Palaniappan, Nachi; Urbano, Teresa Guerrero; et al.
Abstract: Background: Radical (chemo)radiotherapy offers potentially curative treatment for patients with locally advanced laryngeal or hypopharyngeal cancer. We aimed to show that dose-escalated intensity-modulated radiotherapy (DE-IMRT) improved locoregional control. Methods: We performed a phase III open-label randomised controlled trial in patients with laryngeal or hypopharyngeal cancer (AJCC III-IVa/b, TNM 7). Patients were randomised (1:1) to DE-IMRT or standard dose IMRT (ST-IMRT) using a minimisation algorithm, balancing for centre, tumour site, nodal status and chemotherapy use. DE-IMRT was 67.2 gray (Gy) in 28 fractions (f) to the primary tumour and 56Gy/28f to at-risk nodes; ST-IMRT was 65Gy/30f to primary tumour and 54Gy/30f to at-risk nodes. Suitable patients received 2 cycles of concomitant cisplatin and up to 3 cycles of platinum-based induction chemotherapy. The primary end-point was time to locoregional failure analysed by intention-to-treat analysis using competing risk methodology. Findings: Between February 2011 and October 2015, 276 patients (138 ST-IMRT; 138 DE-IMRT) were randomised. A preplanned interim futility analysis met the criterion for early closure. After a median follow-up of 47.9 months (interquartile range 37.5–60.5), there were locoregional failures in 38 of 138 (27.5%) ST-IMRT patients and 42 of 138 (30.4%) DE-IMRT patients; an adjusted subhazard ratio of 1.16 (95% confidence interval: 0.74–1.83, p = 0.519) indicated no evidence of benefit with DE-IMRT. Acute grade 2 pharyngeal mucositis was reported more frequently with DE-IMRT than with ST-IMRT (42% vs. 32%). No differences in grade ≥3 acute or late toxicity rates were seen. Conclusion: DE-IMRT did not improve locoregional control in patients with laryngeal or hypopharyngeal cancer. The trial is registered: ISRCTN01483375. Highlights: This phase III RCT does not support dose escalation using accelerated hypofractionation. No benefit in local tumour control or survival was seen. Two-year local tumour failure rate was approximately 30% in both treatment groups. The larynx was preserved in about 90% patients in both treatment groups.